Modified copolyester film as well as preparation method and application thereof
By introducing 2,5-furandicarboxylic acid and neopentyl glycol into the polyester film, the polarity and hydrophilicity are improved, the problem of insufficient binding force between the polyester film and copper foil is solved, and the modified copolyester is realized The good bonding force between the film and the copper foil improves the energy density and safety of lithium batteries.
Patent Information
- Application Number
- CN202411544560.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-07
AI Technical Summary
The interface bonding force between the existing polyester film and copper foil is poor, resulting in the delamination of the composite fluid collector during the immersion of high-temperature electrolyte, affecting its use in lithium batteries.
By introducing 2,5-furandicarboxylic acid and neopentyl glycol into the polyester molecular chain, the polarity and hydrophilicity of the polyester are enhanced, the crystallinity and melting point are reduced, thereby enhancing the interface interaction force and binding with the copper foil. strength.
Achieve good bonding between the modified copolyester film and copper foil, improve the thermal stability, mechanicality and processability of the film, is suitable for composite fluid-collection substrate materials, and improves the energy density and safety of lithium batteries. sex.
Smart Images

Figure CN119390960A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of current collectors and relates to a modified copolyester film and a preparation method and application thereof. Background Art
[0002] With the continuous development of lithium-ion battery technology and the continuous improvement of the performance of electric vehicles and portable electronic products, there is an urgent need for the next generation of lithium-ion batteries with high energy density and high safety. As an indispensable component of lithium-ion batteries, the current collector not only carries the active material, but also acts as a carrier for electron transfer between the positive and negative electrode materials, establishing the current transmission path between the internal and external circuits.
[0003] Compared with the current collector, the composite current collector can greatly improve the energy density of the battery by reducing thickness and weight, and the insulation and melting properties of the intermediate layer polymer itself can improve the safety of the battery. It has the advantages of high specific energy, high safety and low cost.
[0004] PET (polyethylene terephthalate) film has significant advantages, such as high tensile strength, excellent thermal stability, good durability, excellent physical and chemical properties, low production cost, and amenability to chemical plating and vapor deposition. Therefore, it has become a widely used substrate material for current collectors. However, the interfacial bonding between PET and the metal layer is poor, which can cause delamination of the composite current collector during immersion in high-temperature electrolyte, thus limiting its use in batteries.
[0005] Therefore, there is an urgent need in the art for a polyester film with excellent bonding strength with copper foil for use in composite current collectors. Summary of the Invention
[0006] To address the shortcomings of existing technologies (the regular molecular structure of existing polyesters (such as PET) results in relatively high cohesive energy, a high melting point, and an inert film surface, making it difficult to bond well with copper foil during electroless plating), the present invention aims to provide a modified copolyester film, its preparation method, and its application. The modified copolyester film provided by the present invention exhibits excellent thermal stability, mechanical properties, and workability, and exhibits good adhesion to copper foil. It can be directly used as a substrate for current collectors using electroless plating and vapor deposition, and holds great promise for lightweight, high-energy-density, and low-cost lithium batteries in the future.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a modified copolyester film, wherein the raw materials for preparing the modified copolyester film include a dibasic acid, a diol, and a catalyst;
[0009] The dibasic acid includes 2,5-furandicarboxylic acid and other dibasic acids;
[0010] The diols include neopentyl glycol and other diols.
[0011] During the polyester polymerization process, the present invention introduces 2,5-furandicarboxylic acid and neopentyl glycol, respectively, to enhance the polarity of the polyester and reduce its crystallinity and melting point. This increased polarity helps increase the interfacial interaction between the polyester surface and the copper foil, and improves wettability on the polyester surface, making it easier for the copper foil to form a uniform coating on it, thereby improving adhesion to the copper foil. The reduced crystallinity and melting point of the polyester facilitate softening or partial melting of the film upon contact with the copper foil, increasing the contact area and interdiffusion between the two. This effect may enhance mechanical anchoring and chemical bonding at the contact interface, thereby improving bonding strength.
[0012] Preferably, the other dibasic acid comprises terephthalic acid and / or isophthalic acid.
[0013] Preferably, the other diols include any one of ethylene glycol, propylene glycol or butanediol, or a combination of at least two of them.
[0014] Preferably, the molar ratio of the diol to the dibasic acid is (1.2-1.6):1, for example, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, etc.
[0015] Preferably, based on the total molar number of the dibasic acid as 100%, the molar content of 2,5-furandicarboxylic acid in the dibasic acid is 5% to 40%, for example, 5%, 8%, 10%, 13%, 15%, 18%, 20%, 23%, 25%, 28%, 30%, 33%, 35%, 38%, 40%, etc.
[0016] Preferably, based on the total molar number of diols as 100%, the molar content of neopentyl glycol in the diols is 1% to 10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc.
[0017] Preferably, the catalyst includes any one of antimony glycolate, antimony trioxide, and antimony acetate, or a combination of at least two of them.
[0018] Preferably, the amount of the catalyst added is 0.2 to 0.4 parts per million of the total mass of all raw materials, for example, 0.2 parts per million, 2.5 parts per million, 0.3 parts per million, 3.5 parts per million, 0.4 parts per million, etc.
[0019] Preferably, the modified copolyester film is a modified PET film.
[0020] In a second aspect, the present invention provides a method for preparing the modified copolyester film according to the first aspect, the preparation method comprising the following steps:
[0021] (1) Adding dibasic acid, diol and catalyst into a reactor, beating the pulp, and starting the esterification reaction. The reaction degree is judged according to the amount of water discharged from the esterification reaction. When the reaction degree reaches more than 95%, the esterification reaction is completed;
[0022] (2) After the esterification reaction is completed, the polycondensation reaction begins, followed by discharging, cooling, pelletizing, and drying, and then biaxially stretching to obtain the modified copolyester film.
[0023] Preferably, the esterification reaction in step (1) is carried out under an inert gas atmosphere.
[0024] Preferably, the inert gas comprises nitrogen.
[0025] Preferably, the pressure of the esterification reaction in step (1) is controlled at 340-360 kPa, for example, 340 kPa, 345 kPa, 350 kPa, 355 kPa, 360 kPa, etc., and the temperature is controlled at 260-280 ° C, for example, 260 ° C, 265 ° C, 270 ° C, 275 ° C, 280 ° C, etc.
[0026] Preferably, the polycondensation reaction in step (2) is carried out under vacuum.
[0027] Preferably, the temperature of the polycondensation reaction in step (2) is controlled at 270-290°C, for example, 270°C, 275°C, 280°C, 285°C, 290°C, etc.
[0028] Preferably, the polycondensation reaction time in step (2) is 0.5 to 1.5 h, for example, 0.5 h, 1 h, 1.5 h, etc.
[0029] Preferably, the thickness of the modified copolyester film is 5 to 15 microns, for example, 5 microns, 6 microns, 8 microns, 10 microns, 12 microns, 13 microns, 15 microns, etc.
[0030] In a third aspect, the present invention provides a use of the modified copolyester film as described in the first aspect in a composite current collector.
[0031] Preferably, the composite current collector comprises a base film and a copper layer, and the base film is the modified copolyester film described in the first aspect.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) The present invention introduces 2,5-furandicarboxylic acid into the modified copolyester molecular chain, thereby increasing the polarity and hydrophilicity of the polyester, increasing the interfacial interaction between the polyester surface and the copper foil, and improving the adhesion between the polyester surface and the copper foil;
[0034] (2) The present invention further destroys the regularity of the polyester by introducing neopentyl glycol into the molecular chain of the modified copolyester, reduces the crystallinity and melting point of the polyester, and helps the film to soften or partially melt more easily when in contact with the copper foil, thereby increasing the contact area and mutual diffusion between the two and improving the bonding strength between the film and the copper foil;
[0035] (3) The modified copolyester film obtained by the present invention has good stability, processability, and mechanical properties, and can be used as a composite current collector base material. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a diagram of the synthesis mechanism of the modified copolyester film provided in an embodiment of the present invention.
[0037] Figure 2 Infrared spectra of the modified copolyester films provided in Examples 1-3 of the present invention and Comparative Examples 1-2.
[0038] Figure 3 These are the hydrogen nuclear magnetic spectra of the modified copolyester films provided in Examples 1-3 and Comparative Examples 1-2 of the present invention. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is further described below by way of specific embodiments. It should be understood by those skilled in the art that the embodiments are merely to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0040] Example 1
[0041] In this embodiment, a modified copolyester film is provided. The raw materials for preparing the modified copolyester film include the following components in parts by weight:
[0042] 159.36 parts of terephthalic acid, 85.50 parts of ethylene glycol, 37.44 parts of 2,5-furandicarboxylic acid, 7.55 parts of neopentyl glycol, 0.06 parts of antimony ethylene glycol.
[0043] The preparation method of the modified copolyester film comprises the following steps:
[0044] (1) The above-mentioned raw materials were added to a polyester reactor and beaten evenly. The esterification reaction was pressurized under a nitrogen atmosphere. The pressure was controlled at 350 kPa and the temperature was controlled at 270°C during the esterification process. The reaction degree was judged according to the water output of the esterification reaction. When the reaction degree reached more than 95%, the esterification reaction was terminated;
[0045] (2) After the esterification reaction is completed, the esterification valve is closed, the polycondensation valve is opened, and the reactor is slowly evacuated to a vacuum state using a vacuum pump. The polycondensation temperature is controlled at 280° C. The polycondensation reaction time is 1 hour. The product is then discharged, cooled, pelletized, and dried. Subsequently, the modified copolyester film (with a thickness of 10 μm) is obtained by biaxial stretching.
[0046] Example 2
[0047] In this embodiment, a modified copolyester film is provided. The raw materials for preparing the modified copolyester film include the following components in parts by weight:
[0048] 179.28 parts of terephthalic acid, 89.10 parts of ethylene glycol, 18.72 parts of 2,5-furandicarboxylic acid, 1.51 parts of neopentyl glycol, 0.08 parts of antimony trioxide.
[0049] The preparation method of the modified copolyester film comprises the following steps:
[0050] (1) The above-mentioned raw materials were added to a polyester reactor and beaten evenly. The esterification reaction was pressurized under a nitrogen atmosphere. The pressure was controlled at 340 kPa and the temperature was controlled at 260°C during the esterification process. The reaction degree was judged according to the water output of the esterification reaction. When the reaction degree reached more than 95%, the esterification reaction was terminated.
[0051] (2) After the esterification reaction is completed, the esterification valve is closed, the polycondensation valve is opened, and the reactor is slowly evacuated to a vacuum state using a vacuum pump. The polycondensation temperature is controlled at 270° C. The polycondensation reaction time is 1.5 h. The product is then discharged, cooled, pelletized, and dried, and then biaxially stretched to obtain the modified copolyester film (with a thickness of 10 μm).
[0052] Example 3
[0053] In this embodiment, a modified copolyester film is provided. The raw materials for preparing the modified copolyester film include the following components in parts by weight:
[0054] 119.52 parts of terephthalic acid, 81.00 parts of ethylene glycol, 74.88 parts of 2,5-furandicarboxylic acid, 15.1 parts of neopentyl glycol, 0.12 parts of antimony acetate.
[0055] The preparation method of the modified copolyester film comprises the following steps:
[0056] (1) The above-mentioned raw materials were added to a polyester reactor and beaten evenly. The esterification reaction was pressurized under a nitrogen atmosphere. The pressure was controlled at 360 kPa and the temperature was controlled at 280°C during the esterification process. The reaction degree was judged according to the water output of the esterification reaction. When the reaction degree reached more than 95%, the esterification reaction was terminated;
[0057] (2) After the esterification reaction is completed, the esterification valve is closed, the polycondensation valve is opened, and the reactor is slowly evacuated to a vacuum state using a vacuum pump. The polycondensation temperature is controlled at 290° C. The polycondensation reaction time is 1 hour. The product is then discharged, cooled, pelletized, and dried. Subsequently, the modified copolyester film (with a thickness of 10 μm) is obtained by biaxial stretching.
[0058] Comparative Example 1
[0059] In this comparative example, a modified copolyester film is provided. The raw materials for preparing the modified copolyester film include the following components in parts by weight:
[0060] 159.36 parts of terephthalic acid, 90 parts of ethylene glycol, 37.44 parts of 2,5-furandicarboxylic acid, 0.06 parts of antimony ethylene glycol.
[0061] The preparation method of the modified copolyester film is as described in Example 1.
[0062] Comparative Example 2
[0063] In this comparative example, a modified copolyester film is provided. The raw materials for preparing the modified copolyester film include the following components in parts by weight:
[0064] 200 parts of terephthalic acid, 85.50 parts of ethylene glycol, 7.55 parts of neopentyl glycol, 0.06 parts of antimony glycol.
[0065] The preparation method of the modified copolyester film is as described in Example 1.
[0066] The synthesis mechanism diagram of the modified copolyester film provided in the embodiment of the present invention is as follows: Figure 1 shown.
[0067] The modified copolyester films provided in the examples and comparative examples were subjected to performance tests, and the test methods were as follows:
[0068] (1) Melting point: According to GB / T 14190-2008, the melting point of the modified copolyester film was measured using a differential scanning calorimeter.
[0069] (2) Conductivity: The modified copolyester film was subjected to chemical copper plating, and the specific steps were as follows: the surface of the modified copolyester film was roughened with a mixed aqueous solution containing 10% KMnO4 and 10% NaOH, and then the film surface was rinsed with deionized water; then the surface of the modified copolyester film was sensitized with a 20 mol / L HCl aqueous solution and a 20 g / L SnCl2 aqueous solution, respectively, and then the film surface was rinsed with deionized water; then the modified copolyester film was activated with a 2% AgNO3 aqueous solution, and then the film surface was rinsed with deionized water; then the treated modified copolyester film was immersed in a plating solution and chemically copper plated on the surface (48 g / L potassium sodium tartrate, 25 g / L CuSO4·5H2O, 28 g / L NaOH, 12 mL / L formaldehyde, solvent is water). The surface of the modified copolyester film after copper plating was tested using an SZT-2A four-probe tester, and the average value was taken from five different locations.
[0070] (3) Adhesion: The adhesion of the copper-plated modified copolyester film was tested using an FCF-T01 friction coefficient peel tester according to ASTM D3330.
[0071] (4) Infrared spectrum test: The samples were tested by FT-IR using Nicoleti S5 Fourier transform infrared spectrometer from Thermo Fisher Scientific, USA, with a scanning range of 500 to 4000 cm -1 , the number of scans is 16 times.
[0072] (5) H-NMR test: The dried modified copolyester film was dissolved in a mixed solvent of trifluoroacetic acid and deuterated chloroform (volume ratio 1:9), and the sample was tested at 25°C using an AVANCE III 500 nuclear magnetic resonance spectrometer from Bruker, Switzerland.
[0073] The infrared spectra of the modified copolyester films provided in Examples 1-3 and Comparative Examples 1-2 of the present invention are as follows: Figure 2 As shown, it can be seen that a shift of 1579 cm can be observed in all embodiments and comparative examples. -1 、1505cm -1 and 1470cm -1 The characteristic absorption peak of the benzene ring is 1716 cm -1 The C=O stretching vibration peak in the ester group is the infrared characteristic peak of polyester; in Examples 1-3 and Comparative Example 1, the peaks can be seen at 1030 cm -1 The COC infrared characteristic peak in 2,5-furandicarboxylic acid was observed, proving that the polymerization was successful.
[0074] The nuclear magnetic hydrogen spectra of the modified copolyester films provided in Examples 1-3 and Comparative Examples 1-2 of the present invention are as follows: Figure 3 shown.
[0075] Other performance test results are shown in Table 1.
[0076] Table 1
[0077] Melting point (℃) Conductivity (S / cm) Binding force (F / cm) Example 1 231.1 <![CDATA[1.86×10 5 ]]> 16.9 Example 2 242.2 <![CDATA[8.13×10 4 ]]> 14.6 Example 3 216.8 <![CDATA[3.71×10 5 ]]> 16.5 Comparative Example 1 237.9 <![CDATA[1.99×10 5 ]]> 13.4 Comparative Example 2 224.3 <![CDATA[4.38×10 4 ]]> 10.8
[0078] From the data in Table 1, it can be seen that the modified copolyester films prepared in Examples 1 to 3 of the present invention have a lower melting point (216.8 to 242.2°C) and excellent electrical conductivity (8.13×10 4 ~3.71×10 5 S / cm), bonding strength (14.6~16.9F / cm).
[0079] Compared with Example 1, the melting point of the modified copolyester film provided in Comparative Example 1 is increased, and the bonding strength between the modified copolyester film provided in Comparative Example 1 and the copper foil is significantly worsened; the bonding strength between the modified copolyester film provided in Comparative Example 2 and the copper foil is significantly worsened.
[0080] In summary, the modified copolyester film provided by the present invention has a lower melting point than ordinary PET film, and its thermal stability does not affect the subsequent processing performance; the copper-plated PET film has good electrical conductivity and bonding strength, and can meet the application requirements as a current collector base film.
[0081] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the modified copolyester film, its preparation method, and its application. However, the present invention is not limited to the above-mentioned embodiments, which does not necessarily mean that the present invention must rely on the above-mentioned embodiments in order to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions for the raw materials used, addition of auxiliary components, and selection of specific methods, etc., fall within the scope of protection and disclosure of the present invention.
Claims
1. A modified copolyester film, characterized in that: The raw materials for preparing the modified copolyester film include dibasic acid, diol and catalyst; The dibasic acid includes 2,5-furandicarboxylic acid and other dibasic acids; The diols include neopentyl glycol and other diols.
2. The modified copolyester film according to claim 1, characterized in that: The other dibasic acid includes terephthalic acid and / or isophthalic acid.
3. The modified copolyester film according to claim 1 or 2, characterized in that: The other diols include any one of ethylene glycol, propylene glycol or butanediol, or a combination of at least two of them.
4. The modified copolyester film according to any one of claims 1 to 3, characterized in that: The molar ratio of the diol to the dibasic acid is (1.2-1.6):
1.
5. The modified copolyester film according to any one of claims 1 to 4, characterized in that: The molar content of 2,5-furandicarboxylic acid in the dibasic acid is 5% to 40% based on the total molar number of the dibasic acid as 100%; Preferably, based on the total molar number of diols as 100%, the molar content of neopentyl glycol in the diols is 1% to 10%.
6. The modified copolyester film according to any one of claims 1 to 5, characterized in that: The catalyst comprises any one of antimony glycol, antimony trioxide, and antimony acetate, or a combination of at least two thereof; Preferably, the amount of the catalyst added is 2 to 4 ten thousandths of the total mass of all the raw materials for preparation.
7. The modified copolyester film according to any one of claims 1 to 6, characterized in that: The modified copolyester film is a modified PET film.
8. A method for preparing a modified copolyester film as claimed in any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) Adding dibasic acid, diol and catalyst into a reaction kettle, beating the pulp, and starting the esterification reaction. The reaction degree is judged according to the water output of the esterification reaction. When the reaction degree reaches more than 95%, the esterification reaction is completed; (2) After the esterification reaction is completed, the polycondensation reaction begins, followed by discharging, cooling, pelletizing, and drying, and then biaxially stretching to obtain the modified copolyester film.
9. The preparation method according to claim 8, characterized in that: The esterification reaction in step (1) is carried out under an inert gas atmosphere; Preferably, the inert gas comprises nitrogen; Preferably, the pressure of the esterification reaction in step (1) is controlled at 340-360 kPa, and the temperature is controlled at 260-280° C.; Preferably, the polycondensation reaction in step (2) is carried out under vacuum; Preferably, the temperature of the polycondensation reaction in step (2) is controlled at 270-290°C; Preferably, the polycondensation reaction time in step (2) is 0.5 to 1.5 h; Preferably, the thickness of the modified copolyester film is 5 to 15 microns.
10. Use of the modified copolyester film according to any one of claims 1 to 7 in a composite current collector; Preferably, the composite current collector comprises a base film and a copper layer, and the base film is the modified copolyester film according to any one of claims 1 to 7.
Citation Information
Patent Citations
Transparent modified copolyester and its sheet material preparation method
CN102432855A
Preparation method of high water vapor barrier copolyester
CN116554455A
Cited By
1, 2-propylene glycol containing p-hydroxyphenyl, high-adhesion polyester resin, high-adhesion polyester film and preparation method and application thereof
CN121872894A